(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
There are many definitions which dealt with corruption one of them is an exploitation of power to achieve a private advantage on the other side there are some who believe that it could be achieving in the confrontation lines between public and private sector The economic corruption takes various kinds according to the standards adopted in the division since it may take a legal dimension like falsification and may be have an economic aim like capturing funds and its reasons may be economic wealth in quick or political or social corruption shapes and damaging public funds and others . Corruption leaves different impacts some believe it has positive effects but the fact proves not to be as mere negative effects in positive cover and its most important negative effects are spreading poverty decreasing currency value impeding privatization process and receding development and other . There are a strategies can be adopted to limit corruption phenomenon such as in international strategy represented by cooperation with specialist organizations in combating corruption like transparency organization and Arabic strategy on the Arab region level – and managerial strategy which calls for reforming legal and managerial apparatus in addition to active to role of civil society organizations in limiting such phenomenon .